The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0078774
|View full text |Cite
|
Sign up to set email alerts
|

Human Oral Isolate Lactobacillus fermentum AGR1487 Reduces Intestinal Barrier Integrity by Increasing the Turnover of Microtubules in Caco-2 Cells

Abstract: Lactobacillus fermentum is found in fermented foods and thought to be harmless. In vivo and clinical studies indicate that some L. fermentum strains have beneficial properties, particularly for gastrointestinal health. However, L. fermentum AGR1487 decreases trans-epithelial electrical resistance (TEER), a measure of intestinal barrier integrity. The hypothesis was that L. fermentum AGR1487 decreases the expression of intestinal cell tight junction genes and proteins, thereby reducing barrier integrity. Transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…Stimulation of the TLR2 pathway leads to activation of specific protein kinase C isoforms in vitro , ultimately leading to the sealing of tight junctions and an increase in TEER 28 or prevention of tight junction disruption 7 . Although AGR1487 activated TLR2, the strain disrupted tight junctions and caused a decrease in TEER of epithelial cell monolayers 21 . Caco-2 cells treated with AGR1487 had higher expression levels of genes involved in the p38 MAPK signalling pathway, which leads to tight junction disruption 29 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Stimulation of the TLR2 pathway leads to activation of specific protein kinase C isoforms in vitro , ultimately leading to the sealing of tight junctions and an increase in TEER 28 or prevention of tight junction disruption 7 . Although AGR1487 activated TLR2, the strain disrupted tight junctions and caused a decrease in TEER of epithelial cell monolayers 21 . Caco-2 cells treated with AGR1487 had higher expression levels of genes involved in the p38 MAPK signalling pathway, which leads to tight junction disruption 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacilli found in human faeces can originate from the mouth 19 20 , indicating that this oral isolate may reside in the intestines of the individual from whom it was isolated. AGR1487 was shown to increase intestinal epithelial barrier permeability in vitro , possibly by increasing the turnover of microtubules in the epithelial cells leading to tight junction disassembly 21 . In addition to reducing intestinal epithelial barrier integrity, the in vitro study also suggested that AGR1487 may have a pro-inflammatory effect 21 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A mechanism that was proposed to link to acute symptoms was the breakdown of the intestinal barrier function of the epithelium, leading to increased permeability with bacterial invasion as a possible result (Buret, 2007 ; Ankarklev et al, 2010 ). This was probably inspired by the impressive in vitro phenotypes obtained with certain bacterial, gastrointestinal pathogens and their products/toxins/proteases (Malago et al, 2003 ; Fajdiga et al, 2006 ; Rees et al, 2008 ; Liu et al, 2012 ; Anderson et al, 2013 ; Fiorentino et al, 2013 ) as well as other parasitic protozoans like Entamoeba histolytica, Cryptosporidium parvum , or Blastocystis sp. (Li et al, 1994 ; Leroy et al, 2000 ; Buret et al, 2003 ; Betanzos et al, 2014 ; Wu et al, 2014 ).…”
Section: The Challenge: Symptomatic Vs Asymptomatic Infectionsmentioning
confidence: 99%